Establishing Adiwiyata Schools through raising environmental awareness for students of Madrasah Ibtidaiyah, Wonosuko, Tegalrejo, Magelang - Robiul Fitri Masithoh; Indri Setiyorini; Yohana Dian Maharani; Winda Widianingrum; Imam Satria (Community Empowerment, 2022)
It is everyone's job and obligation to promote a clean and healthy environment. The Adiwiyata school program instills the school community's passion for the environment, as well as caring behavior and environmental culture. The goal of this community service is to raise awareness about the importance of Adiwiyata schools being built with environment care and a waste-free environment. Participatory community empowerment utilizing the Participatory Rural Appraisal (PRA) methodology will be used to carry out this community service activity through multiple stages, including socialization, training, and mentorship. The outcomes of this program demonstrate an increase in the number of schools that are concerned about maintaining a healthy, clean, and comfortable environment.